CENTRAL ASIA THROUGH THE PRISM OF FRENCH ORIENTAL STUDIES - Yorkinoy Nasirdinova (Galaxy International Interdisciplinary Research Journal, 2022)
This article discusses the history of French oriental studies, which originates from the end of the early Middle Ages and found the heyday of the Middle Ages, including the late Middle Ages (IX-XVI centuries). The main events that reflected the acquaintance of France with the East are given.